2007
DOI: 10.2478/s11687-006-0051-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of larval anisakids in blue whiting off Portuguese fish market

Abstract: SummarySpecimens of Micromesistius poutassou (n=238) obtained in a fish market of Oporto, Portugal, were examined for the presence of larval anisakids. Anisakis sp. L 3 larvae (prevalence = 77.7 %; mean intensity = 5.8; mean abundance = 4.5) and Hysterothylacium sp. L 3 larvae (prevalence = 5 %; mean intensity = 4.1; mean abundance = 0.2) were found in body cavity, mesenteries, liver and muscles. The Anisakis sp. intensity and abundance were significantly related to the host body length. The percentage of Anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…Our results show that in December, March and May the parasitic burden in the examined fish was low whereas in February and April there was an increase but this observation is related to the correlation between the size of the fish and the number of parasites. The larval burden was related to host length, as noted also by McGladery and Burt (1985), Abaunza et al, (1995), Adroher et al, (1996), Manfredi et al, (2000) and Cruz et al (2007). As Abaunza et al (1995) review, the direct relationship between infestation level and age or length in the horse mackerel is a prevalent phenomenon in many fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that in December, March and May the parasitic burden in the examined fish was low whereas in February and April there was an increase but this observation is related to the correlation between the size of the fish and the number of parasites. The larval burden was related to host length, as noted also by McGladery and Burt (1985), Abaunza et al, (1995), Adroher et al, (1996), Manfredi et al, (2000) and Cruz et al (2007). As Abaunza et al (1995) review, the direct relationship between infestation level and age or length in the horse mackerel is a prevalent phenomenon in many fish species.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in Moroccan waters, prevalence of anisakids in S. colias varied from 57% to 67.9% (Abattouy et al 2011). High prevalence values were also recorded for anisakids of other fish species from the Portuguese mainland, such as the blue whiting (Micromesistius poutassou, 77.7%), the black scabbardfish (Aphanopus carbo, 100%) (Cruz et al 2007(Cruz et al , 2009) and the blackspot seabream (Pagellus bogaraveo, 100%) (Hermida et al 2012). Moreover, Costa et al (2004) also reported a high prevalence (89.6%) for the blackspot seabream off Madeira Islands, Portugal.…”
Section: Discussionmentioning
confidence: 93%
“…ziphidarum Pagi, Nascetti, Webb, Mattiuci, Cianchi & Bullini, 1988, Pagellus bogaraveo, most larvae encapsulated in fish body cavity, mesenteries, on the ouside of the viscera, Hermida et al (2012b , Saraiva et al (2000b), Silva & Eiras (2003), MacKenzie et al (2008), Cruz et al (2005Cruz et al ( , 2007Cruz et al ( , 2009, (Freitas et al 2009), Santos et al (2009, Hermida et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Hysterothylacium sp., Microchirus azevia, Micromesistius poutassou, Pagellus bogaraveo, Pegusa lascaris (=Solea lascaris), Trachurus trachurus, digestive tract, liver, muscles, encapsulated in body cavity and outside of the viscera, Cruz et al (2005Cruz et al ( , 2007, Marques et al (2006a), Hermida et al (2012a.…”
Section: Methodsmentioning
confidence: 99%